2000
DOI: 10.1177/003435520004300306
|View full text |Cite
|
Sign up to set email alerts
|

Science and Engineering as Viable Career Choices for Students with Disabilities

Abstract: Although the availability of jobs in science and technology fields are abundant, awareness has increased that certain populations (e.g., persons with disabilities) have fewer opportunities to pursue these careers and, consequently, are underrepresented as employees in these fields. The purpose of this study was to examine the perceptions of parents and teachers concerning the following variables as they relate to career entry of persons with disabilities into science and engineering: (a) facility access, (b) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 7 publications
0
32
0
Order By: Relevance
“…Various authors discuss negative systemic issues faced by disabled students in higher education including accessibility, level of participation, stigmatization, lack of financial support, difficulty seeking accommodation [4,[51][52][53][54][55][56], lack of awareness of faculty and peers [51,55], identity of the disabled student [4,52,57], and career choice and development [58][59][60][61]. The Canadian organization, National Educational Association of Disabled Students (NEADS), produced a report in 2018 on the situation of Canadian graduate students with a disability [15] highlighting various problems faced by disabled graduate researchers.…”
Section: Role Identity and Career Developmentmentioning
confidence: 99%
“…Various authors discuss negative systemic issues faced by disabled students in higher education including accessibility, level of participation, stigmatization, lack of financial support, difficulty seeking accommodation [4,[51][52][53][54][55][56], lack of awareness of faculty and peers [51,55], identity of the disabled student [4,52,57], and career choice and development [58][59][60][61]. The Canadian organization, National Educational Association of Disabled Students (NEADS), produced a report in 2018 on the situation of Canadian graduate students with a disability [15] highlighting various problems faced by disabled graduate researchers.…”
Section: Role Identity and Career Developmentmentioning
confidence: 99%
“…Several authors have discussed the limited occupational choices available to individuals with disabilities (e.g., Hahn, 1997;Yuker, 1988). According to Alston and Hampton (2000), parents and teachers believed that people with disabilities have fewer career choices, especially those related to science and engineering. DeLoach (1989) found that employers were concerned that individuals with disabilities were often under-qualified for most careers.…”
Section: Role Entrapmentmentioning
confidence: 99%
“…The study, "Possible Barriers to Persons with Disabilities Acquiring Careers in Science, Engineering, and Math," suggested that shortcomings in the educational system were the main reason students with disabilities do not advance in some academic subjects, particularly in science, mathematics, and engineering [1,2]. Although an analysis of all potential "shortcomings" is beyond the scope of the current discussion, increased accessibility to role models and mentors is one technique to which students respond well.…”
Section: Enlist Mentors and Role Modelsmentioning
confidence: 99%